2014
DOI: 10.1364/ol.39.004927
|View full text |Cite
|
Sign up to set email alerts
|

Using shadows to measure spatial coherence

Abstract: We present a very simple method for measuring the spatial coherence of quasi-monochromatic fields through the comparison of two measurements of the radiant intensity with and without a small obscuration at the test plane. From these measurements one can measure simultaneously the field's coherence at all pairs of points whose centroid is the centroid of the obstacle. This method can be implemented without the need of any refractive or diffractive focusing elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Future work will exploit the large pixel counts of both our camera and DMD array to capture very large 4D datasets (∼Terabytes) and localize millions of point sources in scattering media. We plan to implement faster multiplexing methods [44][45][46] and explore alternate phase-space imaging schemes, such as modified spectrograms [47], light fields [16] and point scanning systems [48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…Future work will exploit the large pixel counts of both our camera and DMD array to capture very large 4D datasets (∼Terabytes) and localize millions of point sources in scattering media. We plan to implement faster multiplexing methods [44][45][46] and explore alternate phase-space imaging schemes, such as modified spectrograms [47], light fields [16] and point scanning systems [48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…Our research explores the scenario in which we have an amplitude mask that is uniformly transparent, except for a small, well-defined obscuration, i.e., A(x) = 1 − a(x) where 0 ≤ a(x) ≤ 1. As previously published, 10 we can get a basic estimate of J, denoted as J 0 , given by…”
Section: Theorymentioning
confidence: 99%
“…10 In addition, we are exploring the possibility of using Fresnel propagation for our theoretical derivation instead of a Fourier transform, so that the measurement can be performed without a lens and not necessarily in the far-field region, something that would be of importance to applications such as the characterization of X-ray sources, for which lenses are not available. Initial work has shown that the derivation is very similar and the result has a form similar to Eq.…”
Section: Future Workmentioning
confidence: 99%
“…Recently, a simple method for efficiently measuring the mutual intensity by using light diffraction around a small obstacle was proposed and demonstrated [8]. This approach has two attractive features.…”
Section: Introductionmentioning
confidence: 99%
“…An extension of this approach was then proposed in which the lens is not required, even though this places some limitations in the range of validity of the method [9]. In this work we combine the advantages of the extended validity that results from using a lens [8] with the improvements that result from using not only diffraction from an obstacle but also from the complementary aperture [9]. In addition, we also incorporate polarization selection elements in order to allow measuring the complete matrix of correlations.…”
Section: Introductionmentioning
confidence: 99%